Pituitary Adenylate Cyclase-activating Polypeptide (PACAP) Treatment during Pre-maturation Increases the Maturation of Porcine Oocytes Derived from Small Follicles - Kyu-Mi Park; Kyoung-Ha So; Sang-Hwan Hyun (The Korean Society of Animal Reproduction and Biotechnology, 2018)
Cellular cyclic adenosine-3' 5'-monophosphate (cAMP) modulator is known as meiotic inhibitor and can delays spontaneous maturation in IVM experiment. Among many cAMP modulators, the role of Pituitary adenylate cyclase activating polypeptide (PACAP) on IVM isn't known. The purpose of this study is to improve the maturation of oocytes derived from follicles ≤ 3 mm in diameter through PACAP as meiotic inhibitor during pre-in vitro maturation (pre-IVM). First, we checked PACAP and its receptors in cumulus cells and, to establish the optimal phase and concentration of PACAP for pre-IVM, we conducted chromatin configuration assessments. As a result, the rate of GV (Germinal Vesicle) according to duration of pre-IVM was significantly decreased 12 h and 18 h after IVM (87.1 and 84.1%, respectively) compared to 0 h (99.4%). When COC was cultured for 18 h, the GV rate in the 1 μM of PACAP treatment group (82.1%) was significantly higher than any other PACAP treatment groups (60.5, 64.1, 74.4 and 69.9 %, respectively). So, we divided into four groups as follows; MF (the conventional IVM group, obtained from follicle from 3 to 6 mm in diameter), SF (the conventional IVM group, obtained from follicle ≤ 3mm in diameter), Pre-SF(-)PACAP (IVM group including 18 h pre-IVM without 1 μM of PACAP, obtained from follicle ≤ 3mm in diameter) and Pre-SF(+)PACAP (IVM group including 18 h pre-IVM with 1 μM of PACAP, obtained from follicle ≤ 3mm in diameter). To examine the effect of PACAP during pre-IVM, we investigated analysis of nuclear maturation, intracellular glutathione (GSH) and reactive oxygen species (ROS) levels. In cumulus cells, PACAP receptors, ADCYAP1R1 and VIPR1 were detected but were not detected in oocytes. After IVM, the Pre-SF(+)PACAP had the highest Metaphase II rate (91.7%) among all groups (P<0.05). The GSH levels in the MF and Pre-SF(+)PACAP were significantly higher than in the other groups (P<0.05) and ROS levels was no significant difference among all groups. In conclusion, these results indicated that even though the oocytes were derived from SF, pre-IVM application of PACAP improved meiotic and cytoplasmic maturation by regulating intracellular oxidative stress.